Exploring Pre-Service Teachers’ Understanding about Scientific Inquiry - Akalamkam, Kalyani (Voices of Teachers and Teacher Educators, 2022)
The aim of this study is to examine the pre-service teachers’ (PSTs) views about scientific inquiry. A descriptive survey is conducted for this purpose using open ended ‘Views About Scientific Inquiry (VASI) Questionnaire’ developed by Lederman et. al (2014). The sample constitutes 107 Pre-service teachers of undergraduate four-year teacher education program. Data was analysed using qualitative research methods by coding and categorising responses into ‘informed’, ‘mixed’ and ‘naïve’ categories. It is found that a majority of PSTs have mixed and naïve views in most of the aspects of scientific inquiry. A majority of PSTs have ‘informed view’ in two aspects of SI namely “all scientific research begins with a question, but does not necessarily need to be tested with hypothesis” and “Inquiry procedures are guided by the question asked”. However, they have naïve and mixed understanding in four aspects— ‘There is no single scientific method’, ‘Inquiry procedures can influence results’, ‘Scientists performing same investigation get same results’ and ‘Scientific data and evidence are not the same’. The study has implications for a pedagogical discourse for promoting scientific inquiry in pre-service teacher education program.